Migraine Genetic Variants Influence Cerebral Blood Flow. Issue 1 (26th September 2019) - Knol, Maria J.; Loehrer, Elizabeth A.; Wen, Ke‐xin; Bos, Daniel; Ikram, M. Kamran; Vernooij, Meike W.; Adams, Hieab H.H.; Ikram, M. Arfan
Abstract : Objective: To investigate the association of migraine genetic variants with cerebral blood flow (CBF). Background: Migraine is a common disorder with many genetic and non‐genetic factors affecting its occurrence. The exact pathophysiological mechanisms underlying the disease remain unclear, but are known to involve hemodynamic and vascular disruptions. Recent genome‐wide association studies have identified 44 genetic variants in 38 genetic loci that affect the risk of migraine, which provide the opportunity to further disentangle these mechanisms. Methods: We included 4665 participants of the population‐based Rotterdam Study (mean age 65.0 ± 10.9 years, 55.6% women). Cross‐sectional area (mm 2 ), flow velocity (mm/s), and blood flow (mL/min) were measured in both carotids and the basilar artery using 2‐dimensional phase‐contrast magnetic resonance imaging. We analyzed 43 previously identified migraine variants separately and calculated a genetic risk score (GRS). To assess the association with CBF, we used linear regression models adjusted for age, sex, and total brain volume. Hierarchical clustering was performed based on the associations with CBF measures and tissue enrichment. Results: The rs67338227 risk allele was associated with higher flow velocity and smaller cross‐sectional area in the carotids ( P minimum = 3.7 × 10 −8 ). Other variants were related to CBF with opposite directions of effect, but not significantly after multiple testing adjustments ( P < 1.4 × 10 −4 ). The migraine GRS was not associated with CBF after multiple testing corrections. Migraine risk variants were found to be enriched for flow in the basilar artery ( λ = 2.39). Conclusions: These findings show that genetic migraine risk is complexly associated with alterations in cerebral hemodynamics.